قواعد المنشأ وتسوية النزاعـات الناتجة عنها في التجارة العربيـة البينيـة - عثمان, سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن الدول العربية تتقدم ولو ببطء نحو إيجاد تكتل اقتصادي عربي، وأهم مظاهر هذا التقدم كان مشروع منطقة التجارة العربية الكبرى الذي يمثل أبسط أشكال التكامل بين الدول العربية، وهذا يعني إزالة بعض القيود الجمركية والإدارية على التجارة بين الدول العربية، علماً أن التجارة البينية بين الدول المنضمة للمنطقة المذكورة تمثل 80% إلى 85% من التجارة العربية البينية. وانطلاقاً من الرغبة في تبسيط الإجراءات التجارية وتحقيق الكفاءة في التجارة على المستوى العربي والدولي، ومن ضرورة المحافظة على المصالح الوطنية لكل الأطراف، والحد من الخلافات الناجمة في نطاق التجارة بين الدول المعنية بسبب هوية السلعة أو ( المنشأ الوطني للسلعة )، يتجه العمل نحو ترسيخ قواعد وأسس تجارية وفق معايير معينة متفق عليها منها: تحديد المنشأ الوطني للسلعة، إذ يعد المنشأ الوطني للسلعة المحور الذي تدور حوله الاتفاقيات التجارية الناظمة لحقوق وواجبات كل طرف. وسنتناول في بحثنا هذا دراسة مفهوم شهادات المنشأ، وقواعد المنشأ، وكذلك إجراءات منح شهادات المنشأ ومنعكساتها على التجارة العربية البينية، وصولاً إلى بعض الحلول والمقترحات للمشاكل الناجمة عن قواعد المنشأ. The Arab countries are advancing, however slowly, towards establishment an Arab economic bloc. The most important aspect of this progress is the project of the Grand Arab Trade Free Area, which represents the simplest form of economic complementarities among the Arab countries. It means the elimination of tariff barriers and administrative restrictions on trade among the Arab countries. Pan–Arab trade among the Arab states joining the Free Area represents 80% to 85% of the pan-Arab trade. Starting out of the desire for simplifying commercial procedures and improving efficiency in trade at Arab and world levels, and because of the necessity of preserving the national interests of all the parties and limiting the disputes in the field of trade among countries owing to the identity of the merchandise (or its country of origin), work is directed towards consolidation of accepted commercial bases and principles. One of these is the specification of the national origin of the merchandise, which is considered the axis around which revolves the trade agreements regulating the right and obligation of each party. In this research, we are going to discuss the concept of certificates of origin, the rules of origin, the procedures of issuing certificates of origin, and the implication for the pan–Arab trade. The paper tries to offer some suggestions and solutions for the problems related the rules of origin.